Case report: Effectiveness of sirolimus in a de novo FAS mutation leading to autoimmune lymphoproliferative syndrome-FAS and elevated DNT/Treg ratio - Gu, Hao; Chen, Zhenping; Ma, Jie; Ma, Jingyao; Fu, Lingling; Zhang, Rui; Wang, Tianyou; Wu, Runhui (Frontiers in Pediatrics, 2022)
Background: The autoimmune lymphoproliferative syndrome (ALPS) is a rare disease characterized by defective function of the Fas death receptor, which results in chronic, nonmalignant lymphoproliferation and autoimmunity accompanied by elevated numbers of double-negative (DN) T cells (T-cell receptor α/β +CD4−CD8−) and an increased risk of developing malignancies later in life. Case Description: Here we report a patient with a de novo FAS mutation with a severe phenotype of ALPS-FAS. FAS gene identified as a novel spontaneous germline heterozygous missense mutation (c.857G>A, p.G286E) in exon 9, causing an amino acid exchange and difference of hydrogen bond formation. Consequently, the treatment with sirolimus was initiated. Subsequently, the patient’s clinical condition improved rapidly. Moreover, DNT ratio continuously decreased during sirolimus application. Conclusions: We described a novel germline FAS mutation (c.857G>A, p.G286E) associated with a severe clinical phenotype of ALPS-FAS. Sirolimus effectively improved the patient clinical manifestations with obviously reduction of DNT ratio.